Postcolonial Ecology & The Cunning of Modernity: Iyat Ekhon Aranya Asil as a Critique of Postcolonial Modernity - Biswas, Debajyoti; Haloi, Jayashree (SARE: Southeast Asian Review of English, 2024)
Abstract: Anuradha Sharma Pujari’s Iyat Ekhon Aranya Asil is a powerful critique of the effect of modernity on postcolonial ecology. The novel explores the relationship between modern city life and the loss of animal habitat in the surrounding hills and forests. The unnamed narrator, a journalist by profession, has been strategically used as a mouthpiece of the author in the novel to critique the underbelly of modern society where the ease of modern life could be sustained only by exploiting land and labour. Drawing from the findings made by decolonial critics like Walter Mignolo and Anibal Quijano on the connection between global modernity, global colonialism, and capitalism, we argue that in a postcolonial context, this double exploitation can be perpetuated only through consent and political manipulation of a complicit public. An ambivalent emotional response by the protagonist in the novel exposes the complicit nature of the privileged class which thrives on such exploitation. In this essay, we shall explore this complex networking which entangles modern life, politics, and landless squatters in a symbiotic relationship that utterly disregards non-human lives. We further argue, in this essay, that emotions like eco-anxiety and solastalgia are foreshadowed by survival needs in postcolonial contexts. Keywords: Solastalgia, Ecoanxiety, Ecopolitics, The Forest Wails, Assam, Colonial Modernity